Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis pada Pelajaran PKN Siswa Kelas V Madrasah Ibtidaiyah - Wilna Wulan Suci Simatupang; Solihah Titin Sumanti; Abdul Gani Jamora Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the effectiveness of the Problem-Based Learning (PBL) model in improving critical thinking skills of students of V MIN 2 Sibolga in the Citizenship Education (PKN) class curriculum. The findings of this study are supported by students' critical thinking skills obtained from the results of the KKM exam and the low level of participation in traditional classroom learning. Using a quantitative approach with a quasi-experimental method and a Non-equivalent Control Group design, this study involved 44 students in the control group (conventional) and the experimental group (PBL). The purpose of the research instrument, namely a double test, was to assess students' critical thinking skills before and after the intervention. The results showed a significant increase in the experimental group that implemented the PBL model. The average post-test score of the experimental group reached 87.50, far exceeding the control group which only reached 60.42. Statistical analysis using the paired sample t-test produced a sig. (2-tailed) value of 0.000, which is smaller than α (0.05). This finding indicates a significant positive effect of the application of the PBL model on improving students' critical thinking skills. The results of this study indicate that the PBL model is effective in improving students' critical thinking skills in PKN classes. This model successfully encourages students to actively participate in their education and develop their analytical skills. This study recommends the use of the PBL model not only in PKN education but also in other subject areas to maximize students' growth in critical thinking. The application of the PBL model can be a potential solution to overcome the challenges of improving students' achievement and critical thinking skills at the highest level of elementary school.